Analisa Kebijakan Publik dari Perspektif Kepemimpinan Melalui Program Pendidikan dan Pelatihan Pegawai Negeri Sipil - Sutarto Mochtar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
This article is aimed for seeking the influence of training and education for structural positions after completing such programme. The influence of training and education programme can be measured easily in terms of achievement of work performance they obtain in the organisation. Furthermore, the length of time is another matter. The changes of the current situation and condition both internal and outside of the organisation have been undergone significantly.